2013
DOI: 10.3906/tar-1207-21
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical characteristics of grafted watermelon on different bottle gourds (Lagenaria siceraria) collected from Mediterranean region of Turkey

Abstract: IntroductionGrafting is widely used in watermelon production to control soil-borne diseases such as Fusarium wilt (Yetisir and Sari 2003;Davis et al. 2008), to increase yield (Lee 1994;Oda 1995;Lee and Oda 2003), and to promote the mineral nutrition uptake (Pulgar et al. 2000), but the objectives of grafting have increased significantly over the years. For instance, grafting has been used to improve resistance against low (Bulder et al. 1990) and high (Rivero et al. 2003) temperatures, to improve resistance ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 57 publications
0
28
1
Order By: Relevance
“…Other clearly negative effects have been reported, such as more fibrous flesh, poor color and taste, increased number of yellowish bands and the occurrence of hollow heart . Changes in mineral composition, sugars, ascorbic acid, citrulline or lycopene content also occur . The impact of grafting on fruit aroma has been studied to a lesser degree, although recent reports show an increase in the concentrations of certain aldehyde volatile compounds in watermelon fruits from plants grafted onto interspecific Cucurbita hybrids and Lagenaria rootstocks .…”
Section: Introductionmentioning
confidence: 99%
“…Other clearly negative effects have been reported, such as more fibrous flesh, poor color and taste, increased number of yellowish bands and the occurrence of hollow heart . Changes in mineral composition, sugars, ascorbic acid, citrulline or lycopene content also occur . The impact of grafting on fruit aroma has been studied to a lesser degree, although recent reports show an increase in the concentrations of certain aldehyde volatile compounds in watermelon fruits from plants grafted onto interspecific Cucurbita hybrids and Lagenaria rootstocks .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, for lycopene content, grafted watermelon fruit showed increased content compared with nongrafted fruit in some studies (Davis et al, 2008;Proietti et al, 2008), while there was no difference in other studies (Bruton et al, 2009;Dabirian et al, 2017;Soteriou and Kyriacou, 2014;Wimer et al, 2015). Further, a decrease in lycopene content has been reported with certain rootstock-scion combinations involving L. siceraria and C. argyrosperma (Candir et al, 2013;Davis and Perkins-Veazie, 2005). For total soluble solids (TSS), rootstock-scion combination can affect results (Davis et al, 2008;Flores et al, 2010;Proietti et al, 2008).…”
mentioning
confidence: 92%
“…For total soluble solids (TSS), rootstock-scion combination can affect results (Davis et al, 2008;Flores et al, 2010;Proietti et al, 2008). Most studies did not find a significant effect in TSS for grafted watermelon with bottle gourd rootstocks (Alan et al, 2007;Alexopoulos et al, 2007;Candir et al, 2013;, however, 0.5% to 1.0% reduction in TSS was reported for grafted compared with nongrafted watermelon treatments in a few studies (Bruton et al, 2009;Davis and Perkins-Veazie, 2005;Kyriacou and Soteriou, 2015;Rouphael et al, 2010). Davis and Perkins-Veazie (2005) further reported that TSS was reduced only in the grafted diploid watermelon treatment.…”
mentioning
confidence: 99%
“…Water soluble dry matter was ranged from 9.70 to 11.13°brix for non-grafted plants and 9.28 to 10.20°brix for grafted plants. Çandır et al [7] found that sugar and organic acid composition of 'Crimson Tide' grafted on different rootstocks ranged for: glucose (1.95-3.14%), fructose (2.69-3.79%), sucrose (1.58-4.69%) as sugar and malic (0.327-0.457%), citric (0.042-0.127%) as organic acid components. There have been some studies on flavour compounds of non-grafted watermelons [8][9][10][11][12][13] that determined aldehyde, alcohol, ketone, furan compounds as main flavour compounds for watermelon.…”
Section: Introductionmentioning
confidence: 99%